EZH2 enables germinal centre formation through epigenetic silencing of CDKN1A and an Rb-E2F1 feedback loop. Issue 1 (December 2017) - Béguelin, Wendy; Rivas, Martín; Calvo Fernández, María; Teater, Matt; Purwada, Alberto; Redmond, David; Shen, Hao; Challman, Matt; Elemento, Olivier; Singh, Ankur; Melnick, Ari
Abstract The EZH2 histone methyltransferase is required for B cells to form germinal centers (GC). Here we show that EZH2 mediates GC formation through repression of cyclin-dependent kinase inhibitorCDKN1A (p21Cip1 ). Deletion ofCdkn1a rescues the GC reaction inEzh2 −/− mice. Using a 3D B cell follicular organoid system that mimics the GC reaction, we show that depletion of EZH2 suppresses G1 to S phase transition of GC B cells in aCdkn1a -dependent manner. GC B cells ofCdkn1a −/− Ezh2 −/− mice have high levels of phospho-Rb, indicating that loss ofCdkn1a enables progression of cell cycle. Moreover, the transcription factor E2F1 induces EZH2 during the GC reaction.E2f1 −/− mice manifest impaired GC responses, which is rescued by restoring EZH2 expression, thus defining a positive feedback loop in which EZH2 controls GC B cell proliferation by suppressingCDKN1A, enabling cell cycle progression with a concomitant phosphorylation of Rb and release of E2F1. The histone methyltransferase EZH2 silences genes by generating H3K27me3 marks. Here the authors use a 3D GC organoid and show EZH2 mediates germinal centre (GC) formation through epigenetic silencing of CDKN1A and release of cell cycle checkpoints.